Aktualisasi Nilai Budaya Siri’ Na Pacce dalam Akuntabilitas Non-Governmental Organization - Ayun Sri Rezkiana; Basuki Basuki (Studi Akuntansi, Keuangan, dan Manajemen, 2024)
Purpose: This research aims to actualize the cultural value of siri' na pacce in the soul of every individual in the accountability of a non-governmental organization (NGO). Research methodology: This type of research is qualitative with a data analysis process using an ethnographic approach which aims to understand the indigenous people's point of view, their relationship with life, to realize their vision of their world. The research was conducted at the gardening learning community Maros Youth Learning Center (MYLC), a learning center under the SRP Payo-payo organization in Maros, South Sulawesi. Results: The research results found that the actualization of siri' na pacce cultural values provides a strong and ethical accountability framework for the NGO. It enhances the running of the organization by fostering a sense of unity to achieve a common mission which is not only symbolized by material accountability, but also by non-material values, such as mutual respect, solidarity, and empathy. In the end, the values of siri' na pacce positively impact the organization's members as a whole. Limitations: Researcher has limitation in interacting with community donors due to limited space which refers to geographical challenges that hinder direct access to donors. Contribution: This research contributes to organizations regarding the implementation of accountability that is imbued with local cultural values, can strengthen accountability and ethics in NGO management because there are intangible, non-material elements.